Developing board game as learning media about waste sorting for fourth grade students of elementary school - Imanuel Vicky Christian; Arie Setiawan Prasida (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
The research aimed to develop a learning media in form of board game about waste sorting for fourth grade students due to the lack of students’ awareness about the purpose of waste sorting. The research used descriptive method to make a description or representation about a fact from real phenomenon, which was about waste sorting that considered less important in society and must be informed since early stage. Strategy of the research was linear strategy that consisted of some phases: (1) Data Collection Phase, (2) Data Analysis and Processing Phase, (3) Product Design Phasee, and (4) Testing Phase. The approach of the research was mix method, combination of qualitative and quantitative. Research subjects at testing phase were 42 students of fourth grade of St. Theresia Marsudirini 77 Salatiga, an Adiwiyata Elementary School. The result of the research showed that, (1) 95 percent of students more interested in learning using a game, (2) “Pilah Sampah” board game was well successfully delivered the learning material about organic and non organic waste, (3) using of board game as learning media alternative was rated good both by teacher and board game expert, based on product questionnaire.